Percolation technique of walker to evaluate Plasmodium vivax Grassi and Plasmodium malariae Laveran in Ashaninkas communities from Satipo (Junín, Peru) - Iannacone O., José A. (1999)
The precoloration technique of Walker was assayed in comparation with the classic Giemsa technique as a differential method to Plasmodium vivax and Plasmodium malariae, in 208 blood samples of seven Ashaninka communities from Rio Tambo district, Satipo, Junin, Peru. Density of parasites by crossing system (+) and by parasites/mL were higher with precoloration of Walker. The prevalence of the parasites was to P. vivax (24,52%) and P. malariae (0,48%) of all samples assayed. Of the seven communities evaluated from Rio Tambo district: Puerto Ocopa, Unión Puerto Ashaninka and Shimavenzo communities showed the highest prevalence of infection with 42,42%, 27,27% y 27,27% respectively. The ages between 0 to 10 and 41-50 years showed the highest prevalence of infection with 31,30% and 40% respectively. The prevalence of infection was independent with the sex. Density of parasites/mL with both techniques were higher in Puerto Prado community; but statistically independent with age and sex. The advantage of precoloration technique of Walker was investigated and some factors that would influence variations in the prevalence of infection and density of parasites of plasmodia assayed dependent on what communities were sampled, age and sex.